O12 Dactylitis is associated with greater disease severity, CRP, ultrasound determined synovitis, and erosive damage in DMARD-naïve early PsA. (26th April 2021) - Dubash, Sayam; Alabas, Oras A; Michelena, Xabier; Garcia-Montoya, Leticia; Wakefield, Richard; Tan, Ai-Lyn; Helliwell, Philip; Emery, Paul; McGonagle, Dennis; Marzo-Ortega, Helena
Abstract: Background/Aims   Dactylitis, a hallmark feature of psoriatic arthritis (PsA), is defined as uniform swelling of a finger or toe ('sausage digit'). Understanding of the phenotypical significance of dactylitis and association with PsA disease activity/severity is still lacking. The aim of this study was to characterise and evaluate a DMARD-naïve early PsA cohort based on the clinical presence or absence of dactylitis. Methods   Early PsA patients achieving CASPAR criteria, were recruited into a prospective observational study; the Leeds Spondyloarthritis Register for Research and Observation (SpARRO). The cohort was evaluated based on presence/absence of dactylitis. Dactylitis was recorded per digit; tender (hot)/ non-tender (cold). Synovitis was graded via the semiquantitative method (0-3) for grayscale (GS) and power Doppler (PD) at 50 joints: wrists, MCP1-5, PIP1-5, DIP2-5, MTP1-5, elbows, knees, ankles, subtalar and talonavicular joints. Bone erosions were determined by US if cortical bone discontinuity was present in two perpendicular planes (longitudinal/transverse). Enthesitis was determined via OMERACT definitions/ modified Glasgow Ultrasound Enthesitis Severity Score (GUESS). Statistical calculations (STATA/SPSS): student's t-test, quantile regression, one-sample tests, Pearson Chi-squared test and Fischer's exact test. Results   Of the 177 PsA patients recruited, PsA with dactylitis recorded significantly higher median difference in TJC (p < 0.01), SJC (p < 0.001), and CRP (p < 0.01) compared to PsA without dactylitis. Dactylitis was present in 81/177 (46%) patients and 214 digits. Multiple digits (>1) were involved in 51/81 (63%) patients, asymmetrical in 52/81 (64%). Dactylitis was more prevalent in toes (146/214; 68.2%) than fingers (68/214; 31.8%). Hot dactylitis was more prevalent (179/214; 83.6%) than cold dactylitis (35/214; 16.4%). The most frequent sites for hot dactylitis were 2 nd finger (23/179; 12.8%), 4 th toe (40/179; 22.3%) and for cold dactylitis, 3 rd finger (2/35; 8.5%), 4 th toe (10/35; 28.5%). Significantly greater US synovitis was identified in PsA with dactylitis (p < 0.01). PsA with dactylitis recorded more patients in high DAPSA state and greater DAPSA scores (median 24.4 vs 20.8; p = 0.07). Joints affected by dactylitis had a high prevalence of US synovitis; 190/255 (74.5%). Synovitis was more prevalent in hot dactylitis than cold dactylitis; 180/227 (79.3%) versus 10/28 (35.7%). Ultrasound erosions were significantly greater in joints in PsA with dactylitis (p < 0.001) and identified in significantly greater PsA patients with dactylitis [22/69 (31.9%) versus 11/86 (12.8%) patients (p = 0.004)]. The sites most prone to erosive damage were MCP2 (9/33, 27.3%), MTP5 (11/33, 33.3%). No significant differences were found for enthesitis determined by OMERACT/ modified GUESS. Conclusion   This study identifies dactylitis as a clinical indicator for an aggressive phenotype with significantly greater TJC, SJC, CRP, US synovitis and US defined erosions in DMARD-naïve early PsA. Longitudinal follow-up will determine if dactylitis represents poor prognosis. Dactylitis may be a useful discriminator for risk stratification in future PsA management strategies and clinical trials. Disclosure   S. Dubash: None. O.A. Alabas: None. X. Michelena: None. L. Garcia-Montoya: None. R. Wakefield: None. A. Tan: None. P. Helliwell: None. P. Emery: None. D. McGonagle: None. H. Marzo-Ortega: None.